Teaching methods and student performance in the Business Accounting Course at Universiti Pendidikan Sultan Idris (UPSI) - P. Letchumanan, Sivaneshan; Mat Norwani, Norlia (International Journal of Accounting, Finance and Business, 2025)
This study explores how different teaching methods influence student performance in the Business Accounting course at Universiti Pendidikan Sultan Idris (UPSI). The research focused on four methods commonly used in accounting courses: traditional lecture-based teaching, blended learning, case studies, and technology-based learning. The aims were to find out which methods students prefer, whether male and female students differ in their preferences and performance, and to what extent each method relates to students’ achievement in the course. A questionnaire was distributed to 90 students to collect information about their background, their views on the four teaching methods, and their performance on a short accounting test. Data were analysed using descriptive statistics, independent sample t-tests, and Pearson correlation analysis. The findings show that students still value the structure of lectures but respond better to more interactive methods. Case studies and blended learning were rated as the most helpful for understanding and applying accounting concepts. Technology-based learning was also welcomed as a support to lectures. Gender differences were small and not statistically significant. The study found a positive relationship between the use of case studies and blended learning with student performance. This study highlights the importance of mixing different teaching methods in accounting education. Combining traditional lectures with case-based activities, online tools, and digital learning creates a richer and more effective learning environment for today’s students.